The Influence of ChatGPT on Writing Anxiety Among English Department Students - Debinda, Phani; La’biran, Roni; Rachel; Rum, Eka Prabawati (Institut Agama Islam Negeri Palopo, 2024)
Writing anxiety is a prevalent problem among students of English, which can discourage their academic performance and writing confidence. As AI-based tools like ChatGPT are becoming more widely used, it is essential to analyze whether such tools have any influencet on the level of students' writing anxiety. This study aims to know the influencet of ChatGPT usage on English students' writing anxiety levels. Specifically, it examines whether there is a significant relationship between the use of ChatGPT and students’ anxiety in academic writing.The research employs a quantitative descriptive approach using a simple linear regression analysis. Data were collected from English students at Universitas Kristen Indonesia Toraja through a questionnaire based on the Second Language Writing Anxiety Inventory(SLWAI).The findings suggest that although there is a trend indicating that using ChatGPT might reduce writing anxiety among students, the influence is not statistically significant. This implies that other factors may play a more crucial role in influencing writing anxiety. Further research with a larger sample and additional variables is recommended to gain deeper insights into this relationship. Keywords: ChatGPT, Writing Anxiety, Influence